The history of qing hao in the Chinese materia medica - Hsu, E (Elsevier, 2006)
Artemisinin is currently used for treating drug-resistant malaria. It is found in Artemesia annua and also in A. apiacea and A. Iancea. Artemisia annua and A. apiacea were known to the Chinese in antiquity and, since they were easily confused with each other, both provided plant material for the herbal drug qing hao (blue-green hao). This article shows, however, that since at least the eleventh centry Chinese scholars recognized the difference between the two species, and advocated the use of A. apicea, rather than A. annua for 'treating lingering heat in joints and bones', and 'exhaustion due to heat/fevers'. The article furthermore provides a literal translation of the method of preparing qing hao for treating intermittent fever episodes, as advocated by the eminent physician Ge Hong in the fourth century CE. His recommendation was to soak the fresh plant in cold water, wring it out and ingest the expressed juice in its raw state. Both findings may have important practical implications for current traditional usage of the plant as an antimalarial: rather than using the dried leaves of A. annua in warm infusions, it suggests that fresh juice extraction from A. apiacea may improve efficacy.